Multifunctional Laser‐Induced Graphene Papers with Combined Defocusing and Grafting Processes for Patternable and Continuously Tunable Wettability from Superlyophilicity to Superlyophobicity. Issue 42 (14th September 2021) - Wang, Yanan; Wang, Guantao; He, Meihong; Liu, Fu; Han, Mingguang; Tang, Tan; Luo, Sida
Abstract: Functional surfaces with tunable and patternable wettability have attracted significant research interests because of remarkable advantages in biomedicine, environmental, and energy storage applications. Based on combined defocusing and grafting strategy for processing laser‐induced graphene papers (LIGPs) with variable surface roughness (58.18–6.08 µm) and F content (0–25.9%), their wettability can be tuned continuously from superlyophilicity (contact angle CA ≈ 0 ° ) to superlyophobicity (CA > 150 ° ), for various liquids with a wide range of surface tensions from 27.5 to 72.8 mN m −1 . In addition to reaching multiple wetting characteristics including amphiphilic, amphiphobic, and hydrophobic–oleophilic states, three designable processes are further developed for achieving LIGPs with various wetting patterns, including hydrophilic arrays or channels, hydrophobic‐to‐hydrophilic gradients, and Janus. Activated by the customly designed structures and properties, multifunctional and multi‐scenario applications are successfully attempted, including 2D‐/3D‐ directional cell cultivation, water transportation diode, self‐triggered liquid transfer & collection, etc. Abstract : By combining defocusing and grafting strategy, laser‐induced graphene papers (LIGPs) are processed with continuously tunable wettability from superlyophilicity to superlyophobicity. Furthermore, three designable processes are developed for achieving LIGPs with variously patterned wettability, including hydrophilic arrays or channels, hydrophobic‐to‐hydrophilic gradients, and Janus for enabling unique functional surfaces, ranging from 3D cell cultivation to directional liquid transportation.